Vision impairment and dual sensory problems in middle age. (29th May 2014) - Dawes, Piers; Dickinson, Christine; Emsley, Richard; Bishop, Paul N.; Cruickshanks, Karen J.; Edmondson‐Jones, Mark; McCormack, Abby; Fortnum, Heather; Moore, David R.; Norman, Paul; Munro, Kevin
Abstract Purpose Vision and hearing impairments are known to increase in middle age. In this study we describe the prevalence of vision impairment and dual sensory impairment in UK adults aged 40–69 years in a very large and recently ascertained data set. The associations between vision impairment, age, sex, socioeconomic status, and ethnicity are reported. Methods This research was conducted using the UK Biobank Resource, with subsets of UK Biobank data analysed with respect to self‐report of eye problems and glasses use. Better‐eye visual acuity with habitually worn refractive correction was assessed with a logMAR chart (n = 116 682). Better‐ear speech reception threshold was measured with an adaptive speech in noise test, the Digit Triplet Test (n = 164 770). Prevalence estimates were weighted with respect to UK 2001 Census data. Results Prevalence of mild visual impairment (VA >0.1 logMAR (6/7.5, 20/25) and ≥0.48 (6/18, 20/60)) and low vision (VA >0.48 (6/18, 20/60) and ≥1.3 (6/120, 20/400)) was estimated at 13.1% (95% CI 12.9–13.4) and 0.8% (95% CI 0.7–0.9), respectively. Use of glasses was 88.0% (95% CI 87.9–88.1). The prevalence of dual sensory impairment was 3.1% (95% CI 3.0–3.2) and there was a nine‐fold increase in the prevalence of dual sensory problems between the youngest and oldest age groups. Older adults, those from low socioeconomic and ethnic minority backgrounds were most at risk for vision problems. Conclusions Mild vision impairment is common in middle aged UK adults, despite widespread use of spectacles. Increased likelihood of vision impairment with older age and with ethnic minorities is of concern given ageing and more ethnically diverse populations. Possible barriers to optometric care for those from low socioeconomic and ethnic minority backgrounds may require attention. A higher than expected prevalence of dual impairment suggests that hearing and vision problems share common causes. Optometrists should consider screening for hearing problems, particularly among older adults.